Sweet and lowdown [videorecording (DVD)] - Allen, Woody, 1935-; Allen, Woody, 1935-; Penn, Sean, 1960-; Morton, Samantha; Thurman, Uma; LaPaglia, Anthony (Columbia Tristar Home Video, 2000)
In the 1930's, the fictional Emmet Ray ruled as the second greatest jazz guitarist in the world. But his reputation was eclipsed by his eccentric career moves, hilarious clashes with gangsters and stormy love affairs with two very different women.